Comparative Analysis of the Quality and Electrical Energy of Wood Waste Briquettes with Natural (Starch) and Synthetic Adhesives (Synthetic Rubber Adhesive) - Arnando, Vito; Jelita, Marhama (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
On average, small and medium-scale wood processing industries produced at least 2 to 4 cubic meters of wood a day, this production produced 0.25 to 2 m3 of wood waste a day. In fact, this waste can be used as a renewable energy source by processing it into briquettes. This research will produce wood waste briquettes using the pyrolysis method from two types of adhesive, namely starch and synthetic rubber adhesive with a composition ratio of 3:1. Apart from that, the resulting briquettes were tested using a bomb calorimeter to obtain the calorific value, water content, ash content, and volatile matter content, and then compared with the SNI 01-6235-2000 standard. The resulting briquettes were then calculated using mathematical calculations for the potential electrical energy they could generate. From laboratory tests, the calorific value, water content, ash content, and volatile matter content of natural adhesive briquettes were obtained at 5194.44 cal/g, 11.3%, 1.36%, and 40.8%, while synthetic adhesive briquettes respectively had values of 6369.46 cal/g, 4.33%, 2.74%, and 25.54%. From these results, synthetic adhesive briquettes had better calorific value, water content, and volatile matter content compared to natural adhesive briquettes. Apart from that, synthetic adhesive briquettes also had greater energy potential with an energy potential of 7,407 kWh/kg compared to briquettes with natural adhesives which only had a value of 6,041 kWh/kg. Thus it can be concluded that synthetic adhesive briquettes are better quality compared to natural adhesive briquettes because they can generate greater energy, and meet 3 of the 4 test parameters based on SNI while natural adhesive briquettes only meet 2 of the same 4 test parameters